Øresund efter Miraklet - Tschemerinsky, Kathrine (Rambam. Tidsskrift for jødisk kultur og forskning, 2014)
Øresund after the Miracle Certain historical narratives have an almost mythological status. This is true for the rescue of the Danish Jews during the Second World War. Not just in Denmark, but internationally as well. Great emotions are at play and disappointments can arise, when eg. historians disapprove of or rewrite popular historical narratives. 2013 marked the 70th anniversary of the action against and the rescue of the majority of the Danish Jews. The anniversary was a good opportunity to get the last witnesses to give testimony. There is, however, very few left who experienced the Second World War and even fewer who saw the escape to Sweden in 1943. This makes it relevant to consider what this event means for the new generations, who did not experience the Holocaust, but for whom the Holocaust is both part of the collective memory as well as a factual historical event. Another point of this article is the dilemmas involved in dealing with the Holocaust as a concept without losing sight of and neglecting the significance of individual destinies.